2020
DOI: 10.1002/cam4.3634
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound radiomics in predicting recurrence for patients with node‐positive head‐neck squamous cell carcinoma treated with radical radiotherapy

Abstract: This prospective study was conducted to investigate the role of quantitative ultrasound (QUS) radiomics in predicting recurrence for patients with node‐positive head‐neck squamous cell carcinoma (HNSCC) treated with radical radiotherapy (RT). The most prominent cervical lymph node (LN) was scanned with a clinical ultrasound device having central frequency of 6.5 MHz. Ultrasound radiofrequency data were processed to obtain 7 QUS parameters. Color‐coded parametric maps were generated based on individual QUS spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Classification the current study than the kNN in the previous study using pretreatment features alone [20]. Also, in a smaller sample size like the present study, individual classifier performances' stability should be interpreted with caution, which will be minimized as more patients are included.…”
Section: Modelmentioning
confidence: 73%
See 1 more Smart Citation
“…Classification the current study than the kNN in the previous study using pretreatment features alone [20]. Also, in a smaller sample size like the present study, individual classifier performances' stability should be interpreted with caution, which will be minimized as more patients are included.…”
Section: Modelmentioning
confidence: 73%
“…In previous studies, QUS-based radiomics have been shown to effectively predict the response to radical RT in patients with HNSCC [18,19]. In a recent study, we have demonstrated the use of QUS-radiomics in predicting the recurrence for HNSCC using pretreatment features [20]. QUS data was obtained from the metastatic lymph node in 51 patients with HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of US radiomics models for prognostic applications in predicting treatment response, locoregional recurrence, and treatment outcomes are summarized in Table 2. Dasgupta et al [38] conducted a prospective study to investigate the role of US radiomics for the pretreatment prediction of recurrence in head and neck cancer patients (clinicaltrials.gov identifier NCT03908684). A total of 51 head and neck cancer patients with a primary site of oropharynx, hypopharynx, and larynx were enrolled in this study.…”
Section: Performance Of Us Radiomics For Response Prediction In Head ...mentioning
confidence: 99%
“…Application of quantitative texture analysis to the QUS imaging has shown to unfold critical biological information that can be modeled effectively to predict biological behavior in breast malignancies [ 12 , 13 ]. Several studies have demonstrated the utility of QUS imaging in predicting treatment response using pretreatment imaging features [ 12 , 14 , 15 , 16 ]. Similarly, the acquisition of QUS features during different treatment modalities (chemotherapy, radiotherapy) reflects ongoing microstructural changes resulting from cell death and can effectively improve the interpretation of clinical outcomes [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%